China's Investment in EU member-states’ Seaports - U Yanbin (Современная Европа)
The article focuses on the Chinese port investment in the EU countries and analyses the motivation and current situation behind it from the Chinese perspective as well as explains the European perception of investment and its future prospect. The study is based on the Chinese and European official documents and Chinese scholars' articles. In recent years, the number of Chinese port investment projects in European countries has been increasing, and the role of ports as hubs in China-EU economic and trade cooperation has become more prominent. However, the negative perception of Chinese port investment in the EU also gradually increases. The EU is concerned that Chinese port investments will challenge the market dominance of European companies in the port shipping sector and cause political division within the EU, even with far-reaching geopolitical implications and security problems. Chinese academics generally believe that China's investment in EU ports is purely a matter of its own economic and trade interests rather than security considerations, and advocate that China and EU should actively promote port cooperation, follow the path of spatial integration and integration of interests, and build a multi-party community of interests for China-EU port cooperation, and require Europe to abandon the direct influence of external factors and commit to fostering a positive interaction between China and EU. It is necessary for Europe to work towards an effective cooperation between China and the EU on economic development issues and political security issues instead of creating a malicious confrontation.